"\\begin{aligned}\n(3x^2y + 2xy + y^3)dx &+ (x^2 + y^2) dy = 0\\\\\n\\\\\nM=3x^2y + 2xy + y^3 &; \\quad N = x^2 + y^2\\\\\nM_y = 3x^2 + 2x + 3y^2 &; \\quad N_x = 2x\\\\\n\\\\\n\\therefore \\dfrac{M_y-N_x}{N} = 3\\\\\n\\\\\nThus,\\ \\mu(x)= e^{\\int{3dx}} &= e^{3x}\n\n\\end{aligned}"Employing "\\mu(x)" into the general equation, we have;
"\\begin{aligned}\ne^{3x}(3x^2y + 2xy + y^3)dx &+ e^{3x}(x^2 + y^2) dy = 0\\\\\n\n\n\\end{aligned}"which, by construction, must be exact. So we seek a function "\\psi" such that;
"\\frac{\\partial\\psi}{\\partial x} =e\r^{3x}(3x\r^2y + 2xy + y\r^3\r)\\\\\n\\frac{\\partial \\psi\r}{\\partial y} = e\r^{3x}\r(x\r^2 + y\r^2\r)"
Integrating the first equation with respect to x and the second equation with respect to y, we get;
"\\psi (x, y) = x^2ye^{3x} + \\frac{1}{3}y^3e^{3x}+h_1(y)\\\\\n\\psi (x, y) = x^2ye^{3x} +\\frac{1}{3}y^3e^{3x}+h_2(x)"
Comparing the two expressions above we observe that we must take a "h_1y = h_2x =" C (a constant).
Thus, function "\\psi" satisfying the exact function must be of the form;
"\\psi (x, y) = e\r^{3x}x^2y + e\r^{3x}y^3 + C"
Thus, the general solution to the equation is of the form;
"e\r^{3x}x\r^2y + e\r^{3x\r}y^3 = C"
Comments
Leave a comment